Affordable housing for first-time homebuyers: Issues and implications from the Malaysian experience - Tan, Teck Hong (2013)
Home ownership improves the home environment in which a child lives, improves a child's cognitive ability and reduces behaviour problems. Home ownership is beneficial not only to households but also to communities as a whole. However, there is little evidence to inform discussion of the challenges of meeting housing needs of first-time homebuyers in conditions of rapid urbanisation. The purpose of this paper is to discuss the challenges of promoting home ownership for first-time homebuyers.This paper is a contribution and stimulus to debate on emerging policy and practice.Drawing upon a case study of Greater Kuala Lumpur, the issue of affordable housing schemes for first-time homebuyers is discussed.The sharp hike in house prices in Malaysian cities has made homeownership a great challenge to most first-time homebuyer to own their home.One way to address the housing needs of young urban household is to increase the supply of affordable housing.But in order to achieve sustainability in housing delivery system, affordable housing schemes must be economically viable. socially acceptable and technically feasible.The government should be transparent about logistics, location, pricing and implementation to ensure that there is action behind the words.